Mainstreaming Sustainability in Public Procurement: Strategic Insights from the Abia State Civil Service - Chiukpai A OKWARA (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
The study investigated sustainable procurement strategies and their impact on organizational performance among 193 respondents from selected Ministries, Departments, and Agencies (MDAs) in Abia State Civil Service, Nigeria. It identified several sustainability measures in use across the public sector, including: integrating environmental factors into purchasing decisions; applying social responsibility criteria (for example, local content and ethical labour standards) during supplier selection; prioritizing suppliers with demonstrated sustainable practices; offering staff training to raise sustainable procurement awareness; and routinely reviewing and updating procurement policies to reflect sustainability goals. Results show a growing commitment to sustainability-oriented procurement across the MDAs. However, correlation analysis found a very weak, statistically insignificant association between sustainable procurement strategies and organizational performance (Pearson’s r = 0.023; Spearman’s ρ = 0.043; p > 0.05), indicating that current implementation levels have not yet produced measurable performance gains. Nevertheless, MDAs that have adopted sustainability-focused procurement reported benefits such as improved operational efficiency, better resource use, and increased public trust. The study recommends stronger policy support, ongoing staff development, and sustained institutional commitment to fully realize the organizational performance advantages of sustainable procurement.